Clinical characteristics and spatial distribution of Visceral leishmaniasis in children in SAo Paulo state: an emerging focus of Visceral leishmaniasis in Brazil - Naufal Spir, Patricia Rodrigues; Prestes-Carneiro, Luiz Euribel; Fonseca, Elivelton Silva [UNESP]; Dayse, Aline; Giuffrida, Rogerio; Zampieri D'Andrea, Lourdes Aparecida [UNESP] (Taylor & Francis Ltd, 2017)
Background: Visceral leishmaniasis (VL) is an emerging zoonosis, and Brazil harbors about 90% of those infected in Latin America. Since 1998, the disease has been spreading quickly in SAo Paulo state, and the western region is considered an emerging focus of VL in Brazil. Our aim was to evaluate the clinical characteristics and spatial distribution of VL in children referred to a public tertiary hospital located in the western region of SAo Paulo state, Brazil. Methods: Medical records of children up to 18years of age who were diagnosed with VL between January 2006 and December 2010 were reviewed. Geospatial analysis was performed using the ArcGIS 10.2 platform. Results: Sixty-three patients were enrolled in the study; the median age was 3.33.3years. The median time interval between the onset of clinical symptoms and diagnosis was 16.1 +/- 11.1days, and the median time in the pediatric ward was 18.0 +/- 9.4days. Liposomal amphotericin B was the first-line treatment in 90.5% of the patients and 9.6% relapsed. One patient died (1.6%), and 19% were submitted to the pediatric intensive care unit. Conclusion: The short interval between the onset of symptoms, diagnosis, and treatment and the reduced number of days of hospitalization certainly influenced the small number of deaths, relapses, and severity among the children infected with VL. However, the disease is spreading fast in the western region of SAo Paulo state. Thus, integrated actions and effective monitoring of the disease are needed to complement curative practices.
Keywords: Visceral leishmaniasis; clinical symptoms; diagnosis; treatment